Teleworking And Work Satisfaction During Covid-19. An Analysis on Sustainability and Future Possible Implementations - Marta Christina SUCIU; Razvan COTESCU; Oana-Raluca TOFAN; Gheorghe Alexandru STATIVA; Mircea Ovidiu MITUCA (Communications of International Proceedings, 2021)
Given that most people employed in Romania before the Covid-19 pandemic spent almost all of their time working, the need for an adequate framework (physically and psychologically) to maintain the productivity of work at home in conditions of telework appeared with the spread of COVID-19. The main objective pursued by this article is to estimate the levels of satisfaction and productivity of telework among Romanian employees, as a result of the COVID-19 pandemic. An opinion poll was used to examine general knowledge about telework, as well as how participants adapted and responded to the challenges they faced. The results of the survey show that it is difficult to adapt. Lack of social and professional contact was the key issue faced by employees. In addition, distance work has had an effect on most people in relation to the need for harmonization between work and personal life. However, more than half of the participants expressed relatively high levels of satisfaction and productivity as a result of their previous experience. We believe that, although it is in its infancy, this study can contribute to more knowledge in the field of telework, by sharing and further debating this knowledge with experienced and interested people working in Romanian companies and government agencies. In the team of authors there are also practitioners who shared their experience through a constructive dialogue. This will be able to facilitate and later allow other experts to use some validated practices and strategies, including in relation to the international experience identified by the analysis of the literature to increase the quality of life of employees, while increasing productivity. The authors opted for a possible implementation of some of the proposed solutions, especially in the medium and long term.
Keywords: Teleworking; Productivity; Sustainability; Coronavirus; ICT; Work-Life Balance; Work Satisfaction